Pretreatment of Rice Straw by Hydrogen Peroxide for Enhanced Methane Yield - Zi-lin SONG; Gai-he YAG; Yong-zhong FENG; Guang-xin REN; Xin-hui HAN (Journal of Integrative Agriculture, 2013)
A pretreatment process for hydrogen peroxide (H2O2) was optimized to enhance the biodegradation performance of rice straw and increase biogas yield. A determination experiment was conducted under predicted optimal conditions. Optimization was implemented using response surface methodology. The effects of biodegradation and the interactive effects of pretreatment time (PT), H2O2 concentration (HC), and substrate to inoculum ratio (S/I) on methane yield were investigated. The lignin, cellulose, and hemicellulose of rice straw were significantly degraded with increasing HC. The optimal conditions for the use of pretreated rice straw in anaerobic digestion were a 6.18-d PT, 2.68% HC (w/w total solid), and 1.08 S/I; these conditions result in a methane yield of 288 mL g−1 volatile solids (VS). A determination coefficient of 95.2% was obtained, indicating that the model used to predict the anabolic digestion process has a favorable fit with the experimental parameters. The determination experiment resulted in a methane yield of 290 mL g−1 VS, 88.0% higher than that of untreated rice straw. Thus, H2O2 pretreatment of rice straw can be used to improve methane yields during biogas production.